Information Sharing and Channel Construction of Supply Chain under Asymmetric Demand Information - Guangdong Wu; Qingshan Kong; Jian-gang Shi; Hamid Reza Karimi; Wei Zhang (Journal of Applied Mathematics)
Information sharing and marketing channel building have become an important problem of supply chain management theory and practice. The research of information sharing focused on traditional channel of supply chain between upstream and downstream enterprises; however, the research ignores the behavior of information sharing with potential entrants and composite structure characteristics about traditional marketing channel with the direct channel. This paper uses the model to research the effects brought about sharing demand information with potential entrants and building marketing channel, which reveals information sharing and channel building mechanism in the supply chain. The study found that the five-force model of Porter regards potential entrants only as a threat that is one-sided. When the channel competitiveness meets certain conditions, manufacturer and retailer will share demand information with potential entrants. Building composite marketing channel is the manufacturer's absolute dominant strategy. Channel construction will increase the entry barriers for potential entrants and weaken the effect of double marginalization; meanwhile, the performance of supply chain will be augmented.